ISSUES OF STUDYING THE SCIENTIFIC HERITAGE OF ABU ISHAQ KALABADI IN MODERN RESEARCHES (Scientific journal of the Fergana State University, 2025)
This article is dedicated to the analysis of the scientific heritage of Abu Ishaq Kalabadi, a prominent 10th-century Sufi theorist and sheikh. Kalabadiy's contribution to the science of Sufism, the works he authored, and the content and essence of those works are revealed in the article. At the same time, the article presents conclusions as a result of research conducted on the interest in his heritage and the studies carried out in this regard. Not only Kalabadiy’s contributions to Sufi science but also his role in the field of Hadith, reflections on his written works, and the unique characteristics of his scientific heritage are thoroughly analyzed.